Two glycerol uptake systems contribute to the high osmotolerance of Zygosaccharomyces rouxii - Dušková, Michala; Ferreira, Célia; Lucas, Cândida; Sychrová, Hana (Molecular microbiology, 2015)
The accumulation of glycerol is essential for yeast viability upon hyperosmotic stress. Here we show that the osmotolerant yeast Zygosaccharomyces rouxii has two genes, ZrSTL1 and ZrSTL2, encoding transporters mediating the active uptake of glycerol in symport with protons, contributing to cell osmotolerance and intracellular pH homeostasis. The growth of mutants lacking one or both transporters is affected depending on the growth medium, carbon source, strain auxotrophies, osmotic conditions and the presence of external glycerol. These transporters are localised in the plasma membrane, they transport glycerol with similar kinetic parameters and besides their expected involvement in the cell survival of hyperosmotic stress, they surprisingly both contribute to an efficient survival of hypoosmotic shock and to the maintenance of intracellular pH homeostasis under non-stressed conditions. Unlike STL1 in Sa. cerevisiae, the two Z. rouxii STL genes are not repressed by glucose, but their expression and activity are downregulated by fructose and upregulated by non-fermentable carbon sources, with ZrSTL1 being more influenced than ZrSTL2. In summary, both transporters are highly important, though Z. rouxii CBS 732(T) cells do not use external glycerol as a source of carbon.
Keywords: koncentrace vodíkových iontů; Zygosaccharomyces; Hydrogen-Ion Concentration; Osmotic Pressure; Osmoregulation; biologický transport; Symporters; fyziologický stres; Biological Transport; osmotický tlak; regulace genové exprese u hub; mikrobiální viabilita; Culture Media; delece genu; organické látky; Gene Expression Regulation, Fungal; Gene Deletion; kultivační média; Stress, Physiological; symportéry; osmoregulace; Glycerol; Microbial Viability; glycerol; Organic Chemicals